An Enhanced Text Steganography Technique (SHA-Logic): Based on Conditional Logic and SHA-3 (Secure Hash Algorithm 3) - Kisakye Diana Michelle; Ocen Gilbert Gilibrays; Odongtoo Godfrey (JISR on Computing)
Text teganography is a method used to hide confidential messages in a message's text without arousing suspicion. This technique has been used in the past, from ancient Greece's scytale tool to modern methods such as Lempel-Ziv-Welch compression and Reflection Symmetry. As digital data continues to be transmitted between devices, it is vulnerable to attack, making text steganography an essential tool for securing data. Over the years, various techniques have been used to achieve this, including substitution, modification, and embedding techniques. However, text steganography still presents challenges, such as easy detection and the trade-off between hiding capacity and quality of the covered medium. Cryptography has been suggested to improve security by encrypting the original message into a cypher text. However, it cannot withstand the advancements in technology that can break cryptographic methods. Therefore, combining cryptography and steganography is always advisable because steganography increases the security of the carrier message as encryption (Cryptography) provides confidentiality. This study explores the various techniques used in text steganography and the challenges present in them to develop a high hiding capacity, robust, and high-quality covered medium text steganography technique that combines both Steganography and Cryptography using a condition Logic and Secure Hashing algorithm.